Contribution of a Simple Bioassay in Effective Therapeutic Drug Monitoring of Posaconazole and Voriconazole. Issue 5 (October 2015) - Tonini, Julia; Bailly, Sébastien; Gautier-Veyret, Elodie; Wambergue, Clémentine; Pelloux, Hervé; Thiébaut-Bertrand, Anne; Cornet, Muriel; Stanke-Labesque, Françoise; Maubon, Danièle
Abstract : Background: With the constantly growing incidence of invasive fungal infections, any failure of antifungal treatment is worrying. Azole antifungals present high variability of their plasma trough concentrations (Cmin ), justifying their therapeutic drug monitoring (TDM). The authors aimed to develop a simple bioassay to determine the in vitro growth inhibition diameter (ID) and to correlate this ID with Cmin in patients treated with voriconazole or posaconazole. Methods: The bioassay determined the ID for Candida parapsilosis using a disk diffusion method. Calibration curves were built for posaconazole and voriconazole in water and in 45% plasma. ID was determined in plasma from patients currently undergoing TDM for posaconazole (n = 73) or voriconazole (n = 90). Results: In water or plasma spiked with antifungals and patient samples, cubic regression between ID and Cmin gave coefficient of determination values of 0.997, 0.999, and 0.819, respectively, for posaconazole and 0.996, 0.990 and 0.925, respectively, for voriconazole ( P < 0.001 for each curve). Calibration curves with or without plasma did not differ. For voriconazole, Cmin of 1 and 4.7 mg/L corresponded to 54% and 90% of maximal ID, respectively. For posaconazole, Cmin of 0.5, 0.7, and 1 mg/L corresponded to 26%, 40%, and 53% of maximal ID, respectively. Conclusions: Bioassay could be useful to better characterize the antifungal therapeutic range and brings additional information to the interpretation of TDM in patients for whom Cmin alone is insufficient to adjust the antifungal dosage.